PERANAN AUDIT INTERNAL DALAM MENUNJANG EFISIENSI DAN EFEKTIVITAS PENGENDALIAN INTERNAL PADA SISTEM PENGGAJIAN PT ILLUMINATI METAMORPHOSIS - Azzahra, Asya; Alyah R, A. Fadilah; Khairurrijal, Khairurrijal; Ramadhani, Dwi Zahra; Ramadhani, Misliyatul (JURNAL LENTERA AKUNTANSI, 2025)
The payroll system is one of the processes most vulnerable to errors and fraud, making effective internal control and the role of internal audit essential to ensure accuracy, transparency, and accountability. This study aims to analyze the role of internal audit in supporting the efficiency and effectiveness of internal control within the payroll system of PT Illuminati Metamorphosis. A descriptive qualitative approach was employed through interviews, observations, and documentation related to payroll procedures and internal monitoring mechanisms. The findings indicate that the implementation of internal audit at PT Illuminati Metamorphosis is not yet fully adequate due to the absence of formal written policies and procedures, as well as insufficient separation of duties. Although internal audit contributes to enhancing the efficiency and effectiveness of the payroll process, improvements are still required, particularly in documentation practices, segregation of duties, and the development of a digital payroll system to strengthen internal control.